Effect of Ball Size on the Microstructure and Morphology of Mg Powders Processed by High-Energy Ball Milling (2021)
ABSTRACT: Commercial powders of pure magnesium were processed by high-energy ball milling. The microstructural and morphological evolution of the powders was studied using scanning electron microscopy (SEM), energy dispersive spectrometry (EDX) and X-ray diffraction (XRD). From the results obtained, it was determined that the ball size is the most influential milling parameter. This was because balls of 1 mm diameter were used after a previous stage of milling with larger balls (i.e., 10 and 3 mm). The powder particles presented an unusual morphology with respect to those observed in the Mg-milling literature and recrystallization phenomena. Moreover, the result strongly varied depending on the ball-to-powder weight ratio (BPR) used during the milling process.